Peripheral nerve ultrasound in amyotrophic lateral sclerosis phenotypes. Issue 5 (14th March 2015) - Schreiber, Stefanie; Abdulla, Susanne; Debska‐Vielhaber, Grazyna; Machts, Judith; Dannhardt‐Stieger, Verena; Feistner, Helmut; Oldag, Andreas; Goertler, Michael; Petri, Susanne; Kollewe, Katja; Kropf, Siegfried; Schreiber, Frank; et al.
ABSTRACT: Introduction: In this study we sought to determine the cross‐sectional area (CSA) of peripheral nerves in patients with distinct subtypes of amyotrophic lateral sclerosis (ALS). Methods: Ulnar and median nerve ultrasound was performed in 78 ALS patients [classic, n = 21; upper motor neuron dominant (UMND), n = 14; lower motor neuron dominant (LMND), n = 20; bulbar, n = 15; primary lateral sclerosis (PLS), n = 8] and 18 matched healthy controls. Results: Compared with controls, ALS patients had significant, distally pronounced reductions of ulnar CSA (forearm/wrist level) across all disease groups, except for PLS. Median nerve CSA (forearm/wrist level) did not differ between controls and ALS. Conclusion: Ulnar nerve ultrasound in ALS subgroups revealed significant differences in distal CSA values, which suggests it has value as a marker of LMN involvement. Its potential was particularly evident in the UMND and PLS groups, which can be hard to separate clinically, yet their accurate separation has major prognostic implications. Muscle Nerve 51 :669–675, 2015